EPISTEMOLOGI DALAM KONSEP ISLAM: EPISTEMOLOGI BAYANI, BURHANI, DAN ‘IRFANI - Frida Rohmatika; Eva Dewi; Afini Nurul Hidayah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Epistemology in the Islamic concept encompasses three main approaches, namely Bayani, Burhani, and ‘Irfani epistemology, each with distinct characteristics and methods in acquiring knowledge. Bayani epistemology focuses on the authority of sacred texts such as the Qur'an and Hadith with a textual and conservative approach. Burhani epistemology emphasizes the use of reason and logic as the primary sources of knowledge, prioritizing demonstration methods and rationality. Whereas 'Irfani epistemology prioritizes intuitive knowledge and direct spiritual experiences (kasyf) that are mystical and Sufi in nature. In the development of Islamic tradition, Bayani and 'Irfani epistemology are more dominant, while the use of reason in Burhani epistemology is less optimal. These three approaches complement each other and form a comprehensive Islamic epistemological framework, distinguishing it from Western epistemology by significantly incorporating normative religious values. This study examines these three epistemologies as a foundation for understanding Islamic knowledge in a holistic and integrative manner.